Rancang Bangun Sistem Informasi Geografis Pemetaan Wilayah Penderita Penyakit Stunting - Amri Muliawan Nur; Fathurrahman Fathurrahman; Muhammad Saipul; Nila Sulastri Oktavia (Fakultas Teknik Universitas Hamzanwadi, 2023)
Stunting is a growth disorder in children and toddlers caused by lack of nutritional intake, so that children's height is stunted compared to children their age. Currently, stunting sufferers in West Sakra District can be said to be quite vulnerable. So it requires intensive treatment and attention quickly and precisely. In mapping the area of stunting sufferers in West Sakra District it is still manual so that in the process of searching for areas with stunting in West Sakra it takes a long time and tends to cause problems. Therefore, a study was conducted to create a geographic information system for mapping the areas of stunting sufferers in West Sakra District. The purpose of this system is to provide convenience and help the West Sakra District, especially the Rensing Health Center, which manages the data. The steps taken in making this system are system requirements analysis, system design, system creation, and system testing. And in making this system, using the PHP programming language and using MySQL as the database